SISTEM INFORMASI GEOGRAFIS PENENTUAN DAERAH POTENSI RAWAN PANGAN (STUDI KASUS: KABUPATEN PONTIANAK) - Sari, Yunitia (Jurusan Informatika Universitas Tanjungpura, 2014)
Food is a basic need for humans. The more advanced a nation, the greater demands for quality of the food they consume will be increase. Nevertheless there are still many places where the unmet food evenly. Food insecurity could cause to hunger, malnutrition and health problems, and worst is death. Food insecurity can be seen in terms of production, consumption and distribution. Geographical mapping activities should be planned and conducted to assist in determining priority areas that potentially have food insecurity. This research aims to map the areas of potential food insecurity in the district of Pontianak and analyze the indicators that have been defined, specifically the access roads, the number of grocery stores, the amount of maternal mortality, malnutrition, electricity, health facilities and poor families. The analysis of composite prioritization is done by using Principal Component Analysis (PCA) and analysis of clusters (clustering). Principal Component Analysis (PCA) is a method used to construct a new variable which is a linear combination of the original variables. To give the accurate results, the variable will be reduced to create a new variable called principal component. Observation Cluster analysis is also used to perform the analysis of existing patterns, classifying objects into groups that have similar and classifying the pattern. This system can help us to manage the tabular data of indicator and displayed as maps and generate reports in tabular form of potentially food-insecure areas. The conclution of this research represent the priority areas of food insecurity are Wajo Hulu, Jungkat, Sei Nipah, Parit Bugis, Galang, Peniraman, Sei Pinyuh, Sei Bakau Besar Laut, Pasir Wan Salim, Penibung, Terusan and Sei Limau. Based on the questionnaire testing, the result shows the average respondent gives 50% percentage point of the importance of this application.